2020
DOI: 10.1002/ajim.23171
|View full text |Cite
|
Sign up to set email alerts
|

Occupational respiratory morbidity among hair and beauty salon workers in Udupi taluk, Karnataka, India

Abstract: Background The Indian hair and beauty salon industry is growing rapidly due to the demand for beauty and personal care services and products. Workers in the industry are vulnerable to several occupational factors such as chemicals, confined space, and poor ventilation. Chemicals in the products used are known or suspected to cause allergies, respiratory, neurological and reproductive health problems and cancer. Methods The present study was carried out to determine the factors associated with the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…The overall prevalence of occupational respiratory morbidity in this study was higher than in a couple of studies conducted in India (12.7%)43 and (19%) 15. However, lower than the studies reported in Palembang, Indonesia (40%)10 and Jeddah, Saudi Arabia (57%) 16.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…The overall prevalence of occupational respiratory morbidity in this study was higher than in a couple of studies conducted in India (12.7%)43 and (19%) 15. However, lower than the studies reported in Palembang, Indonesia (40%)10 and Jeddah, Saudi Arabia (57%) 16.…”
Section: Discussioncontrasting
confidence: 81%
“…Hairdressers are among the higher-risk occupational groups for respiratory problems due to unsafe working conditions, a lack of training and awareness, the use of different chemicals, a lack of regular monitoring and inspections and poor accessibility and use of PPE. 15 38–41 In addition, this group of workers belongs to the informal economy, in which work-related exposure is unregulated and working conditions are substandard. They use a variety of hair products that contain chemicals that can make them vulnerable to respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the occupational health hazards that threatens the hairdressers health, it is important to identify the JNSBU occupational hazards, and define which hazards are predominant and in priority. Training approaches should be developed and appropriate prevention strategies to minimize occupational health hazards (Tomar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%